Enhanced open-circuit photovoltage and charge collection realized in pearl-like NiO/CuO composite nanowires based p-type dye sensitized solar cells. (August 2019) - Tan, Rou; Wei, Zengxi; Liang, Jiaojiao; Lv, Zhigang; Chen, Bo; Qu, Jie; Yan, Weibo; Ma, Jianmin
Graphical abstract: A novel NiO/CuO nanocomposite was well-designed and successfully fabricated as photocathode material of p-DSSCs. Combined with Co 2+ /Co 3+ electrolyte, the devices showed noticeable enhancement of both open-circuit photovoltage and short-circuit photocurrent. Highlights: A novel NiO/CuO nanocomposite was used as photocathode material of p-DSSCs. The devices showed noticeable enhancement of both open-circuit photovoltage and short-circuit photocurrent. A deeper valence-band of NiO/CuO resulted in a 140 mV improvement of photovoltage of p-DSSCs. The hole transport of NiO/CuO nanocomposite was improved due to modified effect by CuO. Abstract: Low open-circuit photovoltage and poor hole transfer character of semiconductors have limited the development of p-type dye-sensitized solar cells (p-DSSCs) owing to the minor energy-gap between the conduction band of NiO and the Nernstian potential of the I3 − /I − electrolyte, as well as the low intrinsic hole-conductivity of NiO semiconductor. Hereby, a novel NiO/CuO nanocomposite was well-designed and successfully fabricated as photocathode material of p-DSSCs. Combined with Co 2+ /Co 3+ electrolyte, the devices showed noticeable enhancement of both open-circuit photovoltage and short-circuit photocurrent. Compared to NiO, a deeper valence-band of NiO/CuO resulted in a 140 mV improvement of photovoltage of p-DSSCs. Electrochemical impedance spectroscopy indiates an improved hole transport of NiO/CuO nanocomposite due to modified effect by CuO. Charge recombinations are also suppressed to achieve increased charge collection efficiencies and improved photoelectrochemical performance.